Pengaruh Perusahan Mebel Terhadap Perekonomian di Kabupaten Gorontalo - Usman Musa Sjahrain (Gorontalo Development Review, 2019)
This article aims to determine the effect on the economy of the furniture company in Gorontalo regency. To analyze this article, using a multiple linear regression method. Through multiple linear regression that capital factor (X1), technology (X2) and raw materials (X3) used furniture (X) together (simultaneously) very significant influence on the Economy particularly Income (Y). Statistics prove the suitability of this model F dual independent test: F2hit = 7.99> Fdaf = 2.89, the hypothesis H1 is accepted on the real level = 0.05 or 5% gave a very significant effect on test results. Double determination coefficient: R2 = 0.6820 or 68.20%. This means that 68.20 percent of the variation of income (Y) can be explained by the capital factor (X1), technology and raw materials (X3) together (simultaneously) used a furniture company (X). Separately simple linear regression analysis that capital factor (X1) used furniture (X) has a very significant influence on the Economy particularly Income (Y). This model is proven by independent testing F1 statistics: Fdaf = 0.30 > F1hit = 0.24 H1 hypothesis is accepted on a real level = 0.05 or 5% gave a very significant effect on test results. The field data show a furniture company in Luwoo village made to do a variety of production, using a workforce of 203 people or 8.90 percent. The average income ranges from 60.000 IDR  to 100,000 IDR  per day.